2020
DOI: 10.15586/jptcp.v27i1.655
|View full text |Cite
|
Sign up to set email alerts
|

Romosozumab (sclerostin monoclonal antibody) for the treatment of osteoporosis in postmenopausal women: A review

Abstract: Romosozumab (ROMO) is a recently approved monoclonal antibody (approved by the U.S. Food and Drug Administration [FDA] in April 2019 and Health Canada in June 2019) for the treatment of osteoporosis in postmenopausal women. ROMO works by selectively inhibiting sclerostin-a glycoprotein that inhibits osteoblasts and further promotes bone resorption. The authors reviewed three phase III clinical trials (Fracture Study in Postmenopausal Women with Osteoporosis [FRAME], Active-Controlled Fracture Study in Postmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Thus, PO-MSCs were expected to play a more critical role in bone healing than BM-MSCs [12,63]. Recently, several studies have found that the sclerostin antibody has clinical implications for the treatment of osteoporosis [64,65]. Thompson et al [66] reported that systemic administration of sclerostin antibody in geriatric mice can enhance the proliferation of osteogenic cells in the periosteum of geriatric mice and can contribute to an increase in cortical bone thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PO-MSCs were expected to play a more critical role in bone healing than BM-MSCs [12,63]. Recently, several studies have found that the sclerostin antibody has clinical implications for the treatment of osteoporosis [64,65]. Thompson et al [66] reported that systemic administration of sclerostin antibody in geriatric mice can enhance the proliferation of osteogenic cells in the periosteum of geriatric mice and can contribute to an increase in cortical bone thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that monthly subcutaneous injections of romosozumab are effective in increasing bone formation and density and decreasing bone resorption—results in keeping with the known effects of sclerostin on bone homeostasis [ 73 ]. However, there is some concern about the potential cardiotoxicity of romosozumab, prompting the need for further observations [ 74 ]. In addition, there is evidence in experimental animals that sclerostin generated in response to TNF-α and IL-1β improves post-traumatic osteoarthritis by inhibiting the activity of proteolytic enzymes involved in cartilage degradation [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that monthly subcutaneous injections of romosozumab is effective in increasing bone formation and density and decreasing bone resorption, results in keeping with the known effects of sclerostin on bone homeostasis [72]. However, there is some concern about potential cardiotoxicity of romosozumab, prompting the need for further observations [73]. Osteoprotegerin-Fc given subcutaneously to mice flown for 12 days in space produced a sustained suppression of bone resorption and, thus, deserves further study [74].…”
Section: Discussionmentioning
confidence: 99%